Constructivism, Zone of Proximal Development and Target in a Multi-Dimensional Classroom - Johnson, Bradley (Journal of the American Academy of Special Education Professionals, 2020)
Constructivism represents a heterogeneous body of theoretical approaches across different disciplines for these alliances, as well as, attracting and antagonizing vast audiences within these disciplines, including psychology and education. A major influence on the rise of constructivism has been the theory and research in human development. Classroom characteristics, including motivation, can affect the perceptions and learning of students. By focusing on these factors within the classroom, teachers and students are able to work in a multidimensional classroom. Multidimensional classrooms have more activities and allow for greater diversity in student abilities performances, as well as being more compatible with constructivist tenants about learning. The Zone of Proximal Development (ZPD) opens the possibility for new interpretations of a development as a social construction and undermines the traditional assumption that development is independent from observers, researchers, and educators who can recognize certain aspects of the activity.